Pengaruh Service Quality, Emotional Attachment, dan Religiosity terhadap Customer Loyalty Nasabah BSI di Jawa Timur dengan Customer Satisfaction Sebagai Variabel Intervening - Ibrahim, Mohamad Rafli; Hasib, Fatin Fadhilah; A'la, Al Ma'rifatul (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2024)
The purpose of this study is to determine the effect of service quality, emotional attachment, and religiosity for the Bank Syariah Indonesia’s customer loyalty using customer satisfaction as a mediating variable. The research method is carried out with a quantitatice approach sourced from primary data, The sample obtained was 297 respondent who were general public who have a relation with the organizer or staff of Masyarakat Ekonomi Syariah jawa Timur. This study uses the SEM-PLS (Structural Equation Modeling – Partial Least Square) analysisi technique using SmartLPLS4. The findings suggest that service quality do not have a significant direct effect on customer loyalty, but have a significant indirect effect on customer loyalty. Emotional attachment and religiosity have a significant direct and indirect effect on customer loyalty mediated by customer satisfaction. The limitation of this study was only examine the customer of Bank Syariah Indonesia in East Java, and only focuses on variables as service quality, emotional attachment, religiosity, customer satisfaction, and customer loyalty. This research implicates that loyalty of the customers may increase from a strong attachment between customer and Bank Syariah Indonesia and their individual devotion to Allah SWT, not by service evaluation. Customer’s feeling when using bank may increase their commitment to Bank Syariah Indonesia